Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America - Lingafelter, Steven W.; Tishechkin, Alexey K. (Zootaxa, 2017)
Two new species of high-elevation Parandrinae (Coleoptera: Cerambycidae) are described from Bolivia and Ecuador, South America. Both species are unusual in having piceous coloration over most of the dorsal surface. Parandra (Tavandra) santossilvai Lingafelter & Tishechkin, new species, is described from Achira, Santa Cruz Province, Bolivia, a site at 2,000 meters elevation. Acutandra caterinoi Lingafelter & Tishechkin, new species, is described from Pichincha Province, Ecuador, from sites between 1,900–2,500 meters. Illustrations, descriptions, diagnoses, and discussion of their generic and subgeneric placements are included.